Sex Education for Autistic Adolescents - Ria Dwi Ismiarti; Munawir Yusuf,; Zaini Rohmad (Journal of ICSAR, 2019)
The first adolescent developmental tasks associated with sex that must be mastered is the formation of new relationship and more mature with the opposite sex. The development of interest in the opposite sex follows a certain pattern, likewise for autistic adolescent who experience growth in their sexual side. Sexuality is the integration of feelings, needs, and desires that shape a person’s unique personality, revealing a person’s tendency to be male or female. Sex, on the contrary, is defined as sex or other activities/events from physical relationship sex itself. Adolescent with autism do not like the adolescent age. Parents who have children with autism have different challenge, especially in providing sexual education to their children. Sexual education for adolescents with autism is very important they are more prone to experience sexual harassment. Sexual education is also important for autistic adolescent to them give an adequate understanding regarding changes in physical, mental, and the emotional maturity associated with sexual problems and provide knowledge about the mistake and sexual perversion so that they can protect themselves against the exploitation that can disrupt the physical and mental health.